The Correlation Between Heavy Metal and Nutrient Content in Plecostomus (Pterygoplichthys pardalis) from Ciliwung River in Jakarta - Elfidasari, Dewi; Ismi, Laksmi Nurul; Shabira, Afina Putri; Sugoro, Irawan (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Most of the rivers’ quality in Indonesia is in highly-polluted status including Ciliwung River in Jakarta. The pollution can affect river ecosystem especially the rivers biota such as plecostomus species that is mostly found in Ciliwung River. The information about correlation between heavy metal and nutrition content in Plecostomus flesh still limited, so the result from this research can give the new information about that. The aims of this research is identifying the effect of the heavy metals towards the contents of protein and fat of plecostomus flesh from Ciliwung River. The analyses methods use X-Ray Fluoresence (XRF) Spectrometer, the analysis of protein using kjeldahl method, and fat analysis using extraction method. The result of this research showed that small-sized plecostomus contained the highest fat and protein compared to medium-sized and big-sized plecostomus. The assumption was the contents of heavy metal which can impede protein and fat absorption. Meanwhile, the content of carbohydrate in small-sized plecostomus was the lowest. The identified type of heavy metal using XRF method was Pb, Hg and Cd with the concentration was higher than the maximum standard (SNI) so that the flesh of plecostomus from Ciliwung River in Jakarta is categorized unsuitable to consumption